Florida Box Turtles (Terrapene carolina bauri) as a potential seed dispersal agent for invasive Beach Naupaka (Scaevola taccada) - Rios, Jordan; Donini, Jordan (Frontiers in Amphibian and Reptile Science, 2025)
Vertebrates are often associated with the dispersal of plant seeds in ecosystems. Although megafauna are often the focus of seed dispersal studies, reptiles, particularly herbivorous and omnivorous turtles, have also been recognized as important dispersal vectors. Specifically, North American Box Turtles (Terrapene sp.) have been investigated as seed dispersal agents; however, findings vary from study to study and even based on plant species. The Florida Box Turtle (Terrapene carolina bauri) has been documented serving as a vector of seed dispersal for several native plant species in southern Florida. In this study we sought to investigate the potential of Terrapene carolina bauri as seed dispersal agents of the invasive Beach Naupaka (Scaevola taccada). We collected ingested S. taccada seeds from box turtle fecal samples and from fruiting trees from August through November 2023 and planted them in an outdoor growing plot to document both success and time to germination. Germination largely occurred within a 3–6 week time frame but continued until week 10. Germination success (%) did not significantly differ between the two study groups with final germination percentages of 52% for ingested seeds and 58% for non-ingested seeds. These results suggest that while ingestion does not significantly impact germination likelihood, seeds consumed by box turtles can still successfully germinate, indicating their potential role in the dispersal of this invasive species across habitats.